Optimization of culture medium for in vitro germination and storage conditions of Exochorda racemosa pollen - Jia, Wenqing; Wang, Yanli; Mi, Zhaorong; Wang, Zheng; He, Songlin; Kong, Dezheng (Frontiers in Plant Science, 2022)
Pollen morphology, pollen vigor, and long-term pollen storage are critical for plant cross-breeding and genetic improvement of Exochorda racemosa. We developed a protocol for viability determination and storage of E. racemosa pollen for breeding new varieties. The medium components for E. racemosa pollen germination was optimized by using an Orthogonal Assay Test Strategy (OATS). The germination rates of E. racemosa pollen were investigated after storing at different temperatures and different storage periods. The size of E. racemosa pollen was medium with three germination ditches, and the sculptural type of pollen was striate. Red ink and 2,3,5-triphenyl tetrazolium chloride (TTC) can effectively distinguish viable pollen from the unviable pollen of E. racemosa. The most suitable medium (CK2) for E. racemosa was composed of 150 g· L–1 sucrose, 100 mg·L–1 boric acid, 150 mg· L–1 Ca(NO3)2 and 50 mg· L–1 GA3. Low-temperature stress produced the greater inhibition of pollen tube growth compared with high-temperature conditions. The CK2 medium at pH 6.5 resulted in the highest pollen germination rate and most extended pollen tube length. The optimal temperature for storage of dried pollen was –80℃ (P<0.01), and the germination rate was 53.60% after storage for 390 days. Thawing in a 35°C water bath produced the best viability of E. racemosa pollen after storage at –20°C and –80°C. The short-term storage of E. racemosa fresh pollen at 4 °C was better than that at –20°C and –80°C (P<0.01). It is possible to evaluate pollen quality and store pollen grains for E. racemosa by the parameters defined in this study.